Algunos factores físicos asociados con la captura de peces en Punta Morales, Golfo de Nicoya - Phillips, Peter C. (1984)
As a sequel to littoral fish community study, the 11 most abundant species were analized using a stepwise multiple regression of capture abundance versus temperature, salinity, site, hour and tide. Two species demonstrated strong seasonality in their abundance. Temperature was he physical factor most highly correlated with capture.